2018
DOI: 10.1055/s-0038-1676344
|View full text |Cite
|
Sign up to set email alerts
|

Human Platelet Protein Ubiquitylation and Changes following GPVI Activation

Abstract: Platelet activators stimulate post-translational modification of signalling proteins to change their activity or their molecular interactions leading to signal propagation. One covalent modification is attachment of the small protein ubiquitin to lysine residues in target proteins. Modification by ubiquitin can either target proteins for degradation by the proteasome or act as a scaffold for other proteins. Pharmacological inhibition of deubiquitylases or the proteasome inhibition of platelet activation by col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 51 publications
1
33
0
Order By: Relevance
“…Ubiquitination can be reversed by the action of deubiquitinating enzymes, which cleave ubiquitin from the substrate protein or edit ubiquitin chains by the removal of single ubiquitin moieties. Deubiquitinating enzymes have also been detected in platelets and pre‐treatment of platelets with deubiquitinase inhibitors results in diminished thrombin‐stimulated platelet adhesion and reduced ADP‐, collagen‐, and thrombin‐induced platelet aggregation …”
Section: Ubiquitination As a Post‐translational Modificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Ubiquitination can be reversed by the action of deubiquitinating enzymes, which cleave ubiquitin from the substrate protein or edit ubiquitin chains by the removal of single ubiquitin moieties. Deubiquitinating enzymes have also been detected in platelets and pre‐treatment of platelets with deubiquitinase inhibitors results in diminished thrombin‐stimulated platelet adhesion and reduced ADP‐, collagen‐, and thrombin‐induced platelet aggregation …”
Section: Ubiquitination As a Post‐translational Modificationmentioning
confidence: 99%
“…In ANKRD26 thrombocytopenia the function of the ubiquitin‐proteasome system in platelets is impaired as evidenced by the accumulation of polyubiquitinated proteins . In addition, it has been observed that even platelet activation itself results in an accumulation of ubiquitinated proteins . This might be contradictory to the fact that platelets release their granule proteins upon activation, resulting in a significant loss in intracellular proteins.…”
Section: Ubiquitination As a Post‐translational Modificationmentioning
confidence: 99%
See 2 more Smart Citations
“…HAP1 lysates were used for GlyGly immunoprecipitation using PTMScan Ubiquitin Remnant Motif Kit (Cell Signaling), according to manufacturer's protocol 45,46 . Briefly, 20 mg of extracts were solubilized and denatured in 10 mL lysis buffer (20 mM HEPES, pH 8.0, 9 M urea, 1 mM sodium orthovanadate, 2.5 mM sodium pyrophosphate, 1 mM β-glycerophosphate), reduced using dithiothreitol (4.5 mM final) for 30 minutes at 55 °C.…”
Section: Identification Of Isgylated Proteins Using Glygly Peptidomicmentioning
confidence: 99%